The city that each one sees, a show inspired by Italo Calvino’s Invisible Cities. (Móin-Móin Magazine - Studies in the Art of Puppetry, 2026)
This article presents and analyzes the play “The City Each One Sees”, developed at FINTA/IFSC -Florianópolis in 2023. The play was inspired by the literary work “Invisible Cities”, by Italo Calvino. It is a narrative performed by glove puppets with diverse characteristics who are in territorial displacement and find a new place to settle. The staging allows us to think about interculturalities and the symbolic dispute over territory, in a comical and reflective way. The proposal reveals multiple voices about the act of inhabiting a city and culminates in a perspective that values ancestral knowledge.
Keywords: puppet theater; glove puppets; migration; interculturality